SWIFT J1756.9−2508: spectral and timing properties of its 2018 outburst. Issue 2 (27th August 2018) - Sanna, A; Pintore, F; Riggio, A; Mazzola, S M; Bozzo, E; Di Salvo, T; Ferrigno, C; Gambino, A F; Papitto, A; Iaria, R; Burderi, L
ABSTRACT: We discuss the spectral and timing properties of the accreting millisecond X-ray pulsar SWIFT J1756.9−2508 observed by XMM–Newton, NICER, and NuSTAR during the X-ray outburst occurred in April 2018. The spectral properties of the source are consistent with a hard state dominated at high energies by a non-thermal power-law component with a cut-off at ∼70 keV. No evidence of iron emission lines or reflection humps has been found. From the coherent timing analysis of the pulse profiles, we derived an updated set of orbital ephemerides. Combining the parameters measured from the three outbursts shown by the source in the last ∼11 yr, we investigated the secular evolution of the spin frequency and the orbital period. We estimated a neutron magnetic field of $3.1× 10^{8}\, \lt B_{ PC}\lt 4.5× 10^{8}\, G$ and measured an orbital period derivative of $-4.1× 10^{-12} \lt \dot{P}_{ orb}\lt 7.1× 10^{-12}$ s s −1 . We also studied the energy dependence of the pulse profile by characterizing the behaviour of the pulse fractional amplitude in the energy range 0.3–80 keV. These results are compared with those obtained from the previous outbursts of SWIFT J1756.9−2508 and other previously known accreting millisecond X-ray pulsars.